The influence of cartilage surface topography on fluid flow in the intra-articular gap. Issue 3 (17th February 2017) - Wu, Yabin; Ferguson, Stephen J.
Abstract: Self-lubrication of a diarthrodial joint is largely attributed to interstitial fluid pressurisation. However, the retention of synovial fluid within the intra-articular gap may also contribute to lubrication. Fluid flow in the intra-articular gap between two micro-rough cartilage surfaces was simulated with a three-dimensional numerical model. Representative surface roughness parameters were incorporated and their relative influence on gap flow resistance was quantified. Resistance changes with decreasing gap height were explored. Cartilage surface micro-topography improves the retention of viscous synovial fluid in the gap, through increased resistance to tangential flow. Local asperity contact greatly increases resistance through tortuosity of the flow path.